Spatio-temporal dynamics of drought in Zimbabwe between 1990 and 2020: a review - Mupepi, Oshneck; Matsa, Mark Makomborero (Spatial information research (Online), 2022)
Drought is ranked one of most devastating natural hazards in the world and this is also true in the context of Zimbabwe due to its constant recurrence. The article assesses spatial and temporal dynamics of drought in Zimbabwe between 1990 and 2020. Literature on spatial and temporal occurrence of drought in Zimbabwe highlights that drought occurrence was temporally and spatially heterogeneous from 1990 to 2020. Drought has been occurring since 1990s but its frequency was low during the 1990–2000 decade and high between 2000 and 2020. The most acknowledged drought was 1991/1992 followed by 1994/1995, 2000/2001, 2001/2002, 2004/2005, 2006/2007 and 2011/2012.However the current decade (2010–2020) is not yet well researched as shown by very low confirmation of drought years. Most of the studied literature confirmed drought conditions in Matebeleland and Masvingo followed by Midlands, Mashonaland East Mashonaland West and Mashonaland Central. Literature showed that the majority of studies on spatial and temporal distribution of drought in Zimbabwe were based on crop failure and livestock death assessments. Few studies used scientific meteorological and remote sensing based techniques to study drought in Zimbabwe and those few studies were conducted during the 2011–2020 decade. Therefore there is need to invest more in drought studies, especially use of remote sensing techniques to ensure effective monitoring of the spatio-temporal occurrence of drought in the country for strategic planning and implementation of drought risk reduction initiatives.